Budgetary impact of incorporating intermittent glucose moni toring for individuals with type 1 diabetes - Carneiro de Freitas Nakata, Kelli; Yugi Nakata, Gilson; Guenkka, Ternize Mariana (JORNAL DE ASSISTÊNCIA FARMACÊUTICA E FARMACOECONOMIA, 2025)
Objective: to evaluate the potential budgetary impact – BI resulting from the incorpora tion of the FreeStyle® intermittent glucose monitoring system for individuals with type 1 diabetes mellitus – DM1. Methods: analyzes were carried out using the Excel application for a time horizon of 5 years from the perspective of the state of Mato Grosso, Brazil. The eligible population, individuals aged 18 or over with DM1 and severe hypoglycemia, was selected with the help of an evidence synthesis. The assumed diffusion rates for years 1 to 5 were: 27%; 30%; 33%; 36% and 40%, respectively based on the frequency with which Brazilian diabetics monitor their glucose; in the acceptance of technology and the proportion of diabetic people with access to consultation and exams. A biva riate sensitivity analysis was performed by modifying the population and implantation rate parameters simultaneously. A scenario using smartphones to replace readers was simulated. Results: The eligible population was 2,522 individuals with an increase of 2.6% in subsequent years. The annual cost for sensors/individual was R7,774.00 and for the reader R299.00/individual for the entire time horizon. In years 1 and 5 the BI was R5,497,228.62 and R8,712,561.00, respectively. Replacing readers with smartphones did not prove to be significant for the period considered. Conclusions: the BI of a possible incorporation of FreeStyle® is significant when compared to the amount of budgetary resources reserved to operationalize the entire pharmaceutical assistance policy in the state of Mato Grosso, Brazil.